Implementation of The Policy of Empowering Creative Economy MSMEs in The Papuan Souvenir Handicraft Sector in Sorong City - Milan E.F Latumeten; Suparno Suparno; Aris Toening W (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the implementation of policies to empower MSMEs in the creative economy of the Papuan souvenir handicraft sector in Sorong City, from a public service perspective. The study uses a mixed-methods approach with an explanatory sequential design. The quantitative approach involved a survey of 30 MSME actors using a Likert-scale questionnaire, which was analyzed using descriptive statistics and Pearson correlation. The qualitative approach involved in-depth interviews with five key speakers and was analyzed using thematic analysis and source triangulation. The study results show a very strong and significant relationship among MSME empowerment, the creative economy, Papuan local wisdom, and the role of local governments. Qualitative findings indicate that the MSME empowerment policy has been in operation. However, it has not been optimal due to limited resources, weak coordination between agencies, and a public service approach that is not fully participatory. The study's implications emphasize the importance of strengthening cross-sector synergy and empowerment approaches grounded in local wisdom to enhance policy effectiveness. The limitations of the study lie in the number of respondents and the fact that the loci are restricted to a single area. Therefore, further research is recommended to expand the study area and use a longitudinal approach to obtain a more comprehensive understanding.